Pelatihan Membuat Gula Aren Rasa Jahe Rempah Bagi Pelaku UMKM Gula Aren di Margosari Limbangan Kendal - Ninik Dwi Atmini; Heru Yulianto; Deddy Krisdiyanto (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2024)
Margosari Village, Limbangan District, Regency has abundant natural potential, including sugar palm trees which are used to make palm sugar. Palm sugar producers are monitored by the local Village Government in the Margosari Village Palm Sugar Center. This quality and original production of palm sugar is not matched by an adequate selling price. This service activity which is packaged in the form of training is intended to provide education and training on processing palm sap and with a touch of product innovation so that it can increase the selling price of palm sugar. Training on cooking palm sap with the addition of red ginger juice, turmeric, ginger, galangal, lemongrass and producing a finished product in the form of spiced ginger flavored palm sugar in one drink portion size. The training participants are partners of the Service Team who are SMEs palm sugar producers. The training method uses the participatory learning and action (PLA) method. Participants are actively involved in training activities. The training consists of stages of pre-training evaluation activities, presentation of material, explanation of the tools and materials needed, demonstration of making products, discussion of training production results and post-training evaluation. The training activity ran smoothly from start to finish. It is hoped that the results of the training will continue so that partners will be interested in continuing production and making it a commercial business that is more profitable than producing palm sugar traditionally. After the training activities, the service team is still providing assistance so that the results of the partners' independent production are better. Assistance continues with consultations from partners regarding the net weight of the product and determining the selling price, and how to market the finished product to a wide audience. This positive partner response will be interesting to continue providing services to the community with other themes that are in line with the service roadmap in managing SMEs, such as assistance with attractive product packaging, business legal aspects, and digital-based marketing.